Lithium ion battery with high energy density

By combining lithium iron phosphate and lithium-rich oxide in the positive electrode sheet of lithium-ion battery, and using artificial graphite in the negative electrode sheet, combined with continuous grading technology, the problem of improving the energy density of lithium-ion batteries is solved, and a comprehensive improvement of high energy density, good cycle stability and rate performance is achieved.

CN119812434AActive Publication Date: 2025-04-11EVE POWER CO LTD

Patent Information

Application Number
CN202411959799.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The energy density of existing lithium iron phosphate-graphite system lithium-ion batteries has approached the conventional upper limit, which is difficult to further improve, affecting their performance in application scenarios such as electric vehicles.

Method used

By combining lithium iron phosphate and lithium-rich oxide in the positive electrode sheet, the mass content of lithium-rich oxide is controlled between 0.2 and 20%, and artificial graphite is used in the negative electrode sheet, combined with continuous grading technology to improve the density of the positive electrode sheet.

Benefits of technology

It significantly improves the energy density of lithium-ion batteries, improves cycle stability and rate performance, and avoids performance degradation caused by over-compression density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812434A_ABST
    Figure CN119812434A_ABST
Patent Text Reader

Abstract

The invention provides a high-energy-density lithium ion battery, which comprises a positive plate and a negative plate, the positive plate comprises a positive active material, and the positive active material comprises lithium iron phosphate and a lithium-rich oxide; in the positive plate, the mass content of the lithium-rich oxide is 0.2-20%; the negative plate comprises a negative active material, and the negative active material comprises artificial graphite. The lithium iron phosphate and the lithium-rich oxide are matched, and the content of the lithium-rich oxide in the positive plate is limited, so that the lithium-rich oxide can be promoted to release active lithium ions in the first charging process, irreversible lithium loss during formation of a negative electrode SEI film is effectively compensated, and the energy density of the lithium ion battery is remarkably improved. In addition, artificial graphite is introduced into the negative plate, and the negative plate is matched with the positive plate, so that the energy density of the lithium ion battery can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a lithium-ion battery with high energy density. Background Art

[0002] Lithium iron phosphate batteries are widely favored for their high safety performance and long cycle life, but the current lithium iron phosphate-graphite system has approached the conventional energy density upper limit of 430Wh / L. However, improving the energy density of lithium-ion batteries is very important for a variety of application scenarios. For example, by increasing the energy density, more electrical energy can be stored without increasing the volume and weight of lithium-ion batteries. This can promote the application of lithium-ion batteries. Specifically, for electric vehicles, high-energy-density lithium-ion batteries can provide longer driving distances or stronger energy output after a single charge, which means that electric vehicles can have higher convenience, faster acceleration performance and better climbing ability.

[0003] Therefore, in order to break through the conventional energy density bottleneck of lithium iron phosphate batteries, the industry has adopted a variety of strategies to improve the volume energy density of batteries. For example, exploring new positive and negative electrode materials such as silicon-based negative electrode materials, however, the volume expansion of silicon during the charging and discharging process (up to 300-400%), poor conductivity, and unstable interface with the electrolyte affect the commercial application of silicon-based negative electrode materials.

[0004] Alternatively, by optimizing the internal structure of lithium-ion batteries and reducing the use of inactive materials, such as electrolytes and separators, the proportion of active materials can be increased to improve energy density. However, this method may affect the thermal stability and cycle life of lithium-ion batteries, and requires strict safety and reliability testing to meet market and regulatory requirements. Therefore, this method requires long-term experimental verification and cannot be quickly commercialized.

[0005] Alternatively, the energy density of lithium-ion batteries can be improved by designing high compaction density pole pieces. Ideally, increasing the compaction density can increase the content of active materials per unit volume, thereby increasing the energy density of lithium-ion batteries. However, excessively increasing the compaction density of pole pieces may lead to a series of adverse effects, which in turn reduces the overall performance of lithium-ion batteries. Summary of the invention

[0006] In order to improve the energy density of a lithium ion battery, the present invention provides a lithium ion battery with high energy density.

[0007] According to one aspect of the present application, a high energy density lithium-ion battery is provided, which includes a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate and lithium-rich oxide. In the positive electrode sheet, the mass content of the lithium-rich oxide is 0.2 to 20%; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes artificial graphite.

[0008] During the first charge and discharge process of lithium-ion batteries, the electrode material and the electrolyte will react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material, which will cause a large loss of active lithium ions in the battery, resulting in a low energy density of the lithium-ion battery. The present invention promotes the release of active lithium ions from the lithium-rich oxide during the first charge process by combining lithium iron phosphate and lithium-rich oxide, and limiting the content of the lithium-rich oxide in the positive electrode sheet, thereby effectively compensating for the irreversible lithium loss of the negative electrode artificial graphite when the SEI film is formed during the first charge and discharge, thereby significantly improving the energy density of the lithium-ion battery. Among them, the general formula of lithium-rich oxide is Li x M y O z , M is a transition metal, M includes at least one of Fe, Ni, Mn, and Co. When the stoichiometric ratio of lithium atoms to the transition metal is x / y≥2, it can be called a lithium-rich oxide.

[0009] Preferably, in the positive electrode active material, the mass content of the lithium-rich oxide is 0.2-10%.

[0010] Preferably, the following conditions are met in the positive electrode active material: the mass content of primary particles with a particle size of <0.2 μm of the positive electrode active material is 35-45%; and / or, the mass content of primary particles with a particle size of 0.2-2 μm of the positive electrode active material is 45-65%; and / or, the mass content of primary particles with a particle size of >2 μm of the positive electrode active material is 0-30%. The present invention continuously grades the lithium iron phosphate and lithium-rich oxide in the positive electrode active material in the positive electrode sheet, that is, the large, medium and small particle sizes of the positive electrode active material are combined in a certain proportion, so that more lithium iron phosphate and lithium-rich oxide particles can be filled in the same electrode sheet volume, thereby further improving the density of the positive electrode sheet, thereby improving the energy density of the lithium-ion battery.

[0011] Preferably, the particle size of the primary particles of the lithium-rich oxide is 0.05 to 30 μm.

[0012] Preferably, the lithium-rich oxide includes at least one of lithium-rich lithium iron oxide (Li5FeO4, LFO), lithium-rich lithium nickel oxide (Li2NiO2, LNO), and lithium-rich lithium cobalt oxide (Li6CoO4, LCO).

[0013] Preferably, the particle size of the primary particles of lithium-rich lithium iron oxide is 0.05 to 30 μm; and / or, the particle size of the primary particles of lithium-rich lithium nickel oxide is 0.05 to 30 μm; and / or, the particle size of the primary particles of lithium-rich lithium cobalt oxide is 0.05 to 30 μm.

[0014] The material chemical properties of different lithium-rich oxides are different, so it is necessary to further optimize the performance of lithium-ion batteries by controlling the particle size of different lithium-rich oxides. Specifically, after the first charge and discharge of LFO, its chemical formula changes from Li5FeO4 to LiFeO2, and the crystal structure undergoes irreversible deformation, which causes the volume of LFO particles to shrink, leaving larger pores in the electrode. The present invention, by preferably selecting an ultra-large LFO with a primary particle size of 2 to 30 μm, utilizes the volume shrinkage characteristics during the first charge and discharge to effectively improve the wettability of the electrolyte in the positive electrode sheet and improve the cycle stability. At the same time, the preference for ultra-large particle LFO is conducive to constructing a grading effect, reducing the use of ultra-large particle lithium iron phosphate with poor cycle characteristics, so as to improve the energy density of lithium-ion batteries and enhance the cycle stability.

[0015] In addition, the present invention finds that LNO with a small particle size has high rate and high capacity characteristics. By introducing LFO or LNO with a specific size, it helps to improve the cycle stability and rate performance of lithium-ion batteries.

[0016] Preferably, the following conditions are met in the positive electrode active material: in the primary particles of the positive electrode active material with a particle size of <0.2 μm, the lithium-rich oxide includes lithium-rich nickelate; and / or, in the primary particles of the positive electrode active material with a particle size of 0.2 to 2 μm, the lithium-rich oxide includes lithium-rich nickelate; and / or, in the primary particles of the positive electrode active material with a particle size of >2 μm, the lithium-rich oxide includes lithium-rich lithium ironate. The present invention achieves a high energy density of a high lithium-ion battery by filling lithium-rich oxides of different particle sizes in lithium iron phosphate.

[0017] Preferably, the lithium-rich oxide includes lithium-rich nickel oxide and lithium-rich iron oxide, and the mass ratio is 5-8:2-5. The present application helps to maintain the high energy density of lithium-ion batteries while improving the rate performance of lithium-ion batteries by introducing a specific ratio of LFO and LNO into the positive electrode sheet.

[0018] Preferably, the following conditions are met in the positive electrode active material: in the primary particles of the positive electrode active material with a particle size of <0.2μm, the mass content of the lithium-rich oxide is ≤30%; and / or, in the primary particles of the positive electrode active material with a particle size of 0.2 to 2μm, the mass content of the lithium-rich oxide is ≤30%; and / or, in the primary particles of the positive electrode active material with a particle size of >2μm, the mass content of the lithium-rich oxide is ≤50%.

[0019] Preferably, the compaction density of the positive electrode sheet is 2.2 to 3.1 g / cm 3 .

[0020] Preferably, the method for preparing the positive electrode sheet comprises the following steps: the first step, positive electrode homogenization: adding the conductive agent to N-methylpyrrolidone (NMP), stirring at a low speed of 2.0 to 5.0 m / s for 0.5 to 3 hours; then, lithium iron phosphate and lithium-rich oxide are sequentially added into the reaction system according to the above ratio, and continue to stir at a low speed of 2.0 to 5.0 m / s for 0.5 to 3 hours; then, the stirring line speed is increased to 10 m / s to 25 m / s, and stirred for 0. 5 hours to 3 hours; adding PVDF into the reaction system, stirring at a high speed of 10m / s to 25m / s for 1.0 hour to 8 hours; then adding NMP to adjust the viscosity to 5000 to 25000mPa·s to obtain positive electrode slurry; the second step, positive electrode coating: double-sided coating of the above positive electrode slurry on the front and back sides of the carbon-coated aluminum foil to obtain a positive electrode wet film, wherein the thickness of the carbon-coated aluminum foil is 10 to 15μm; drying the positive electrode wet film through drying treatment to obtain a positive electrode sheet, which can be stored in a roll.

[0021] Preferably, the median particle size D of the artificial graphite is 50 3~25μm.

[0022] Preferably, the compaction density of the negative electrode sheet is 1.4 to 1.9 g / cm 3 .

[0023] Preferably, the method for preparing a negative electrode sheet comprises the following steps: the first step, negative electrode homogenization: artificial graphite and conductive agent are added to deionized water in sequence, and then stirred at a linear speed of 2.0 to 5.0 m / s for 0.5 to 3 hours; CMC is added to the reaction system, and stirred at a linear speed of 5 to 15 m / s for 0.5 to 3 hours; SBR is then added to the reaction system, and stirred at a linear speed of 5 to 20 m / s for 1 to 8 hours; deionized water is added to adjust the viscosity to 3000 to 8000 mPa·s to obtain a negative electrode slurry; the second step, negative electrode coating: the above-mentioned negative electrode slurry is double-sidedly coated on the front and back sides of the copper foil to obtain a negative electrode wet film, wherein the thickness of the copper foil is 4.5 to 8 μm; after the negative electrode wet film is dried by drying treatment, a negative electrode sheet is obtained, which can be stored in a roll. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The cycle capacity retention rate diagram of treatment group 1B, treatment group 2B, and treatment group 3B of the present invention;

[0025] Figure 2 This is a graph of calibrated gram capacity at different rates for treatment group 1B, treatment group 2B, and treatment group 3B of the present invention. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.

[0027] Example 1

[0028] Treatment Group 1A

[0029] 1. Raw materials for preparing positive and negative electrodes

[0030] The materials required for preparing the positive electrode sheet and the negative electrode sheet in this embodiment are shown in Table 1 and are prepared according to the formula provided in Table 1. The ratio in Table 1 refers to the mass ratio of the material for preparing the positive electrode sheet in the positive electrode sheet and the mass ratio of the material for preparing the negative electrode sheet in the negative electrode sheet. In addition, the gradation of the primary particles in the positive electrode active material is shown in Table 2, wherein the primary particle size of lithium-rich ferrite (LFO) ranges from 2 to 5 μm.

[0031] Table 1. Raw materials for preparing positive and negative electrodes in treatment group 1A

[0032]

[0033] Table 2. Grading of positive electrode active materials in treatment group 1A

[0034] Particle size Quality content materials <0.2μm 40% LFP 0.2~2μm 30% LFP >2μm 30% LFP+LFO

[0035] 2. Preparation of positive electrode

[0036] The first step is positive electrode homogenization: add the conductive agent to N-methylpyrrolidone (NMP) and stir at a low speed of 2.0 m / s for 1.5 hours; then, add lithium iron phosphate and lithium-rich oxide into the reaction system in the above ratio, and continue to stir at a low speed of 3.0 m / s for 2 hours; then increase the stirring speed to 18 m / s and stir for 3 hours; add PVDF into the reaction system and stir at a high speed of 20 m / s for 6 hours; then add NMP to adjust the viscosity to 15000 mPa·s to obtain positive electrode slurry;

[0037] The second step is positive electrode coating: the positive electrode slurry is double-sidedly coated on the front and back sides of the carbon-coated aluminum foil to obtain a positive electrode wet film, wherein the thickness of the carbon-coated aluminum foil is 12 μm; the positive electrode wet film is dried by drying to obtain a positive electrode sheet, which can be stored in a roll.

[0038] 3. Preparation of negative electrode sheet

[0039] The first step is to homogenize the negative electrode: artificial graphite and conductive agent are added to deionized water in sequence, and then stirred at a linear speed of 2.0 m / s for 1.5 hours; CMC is added to the reaction system and stirred at a linear speed of 10 m / s for 2 hours; SBR is then added to the reaction system and stirred at a linear speed of 15 m / s for 6 hours; deionized water is added to adjust the viscosity to 5000 mPa·s to obtain the negative electrode slurry;

[0040] The second step is negative electrode coating: the negative electrode slurry is double-sidedly coated on the front and back sides of the copper foil to obtain a negative electrode wet film, wherein the thickness of the copper foil is 6 μm; the negative electrode wet film is dried by drying to obtain a negative electrode sheet, which can be stored in a roll.

[0041] 4. Preparation of Lithium-ion Batteries

[0042] The above positive electrode sheet and negative electrode sheet are rolled into electrodes with a certain porosity; wherein the porosity of the positive electrode sheet is 22.5% (corresponding to the compaction density of the positive electrode sheet of 2.65g / cm 3 ), the negative electrode sheet porosity is 17.2% (corresponding to the compaction density of the negative electrode sheet is 1.80g / cm 3 ), both pole pieces are stored in rolls. Subsequently, the positive pole piece and the negative pole piece are cut / sheeted, wound, pole ear welded, baked, and shelled, and then an appropriate amount of electrolyte is injected into the aluminum-plastic packaging shell, and the battery cell is vacuum-stabilized, edge-sealed, formed, evacuated, sealed, aged at high temperature, capacity-divided, and screened to obtain a lithium-ion battery. The electrolyte formula is: a mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) is used as an organic solvent; vinylene carbonate (VC), fluoroethylene carbonate (FEC), and vinyl sulfate (DTD) are used as additives, and the concentration of LiPF6 in the electrolyte is 1 mol / L.

[0043] Treatment Group 2A

[0044] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that when preparing the positive electrode sheets, the mass content of LFO in the positive electrode sheets is 2.5% (achieved by correspondingly reducing the content of LFP). In addition to the above differences, the operation steps of preparing the positive electrode sheets, negative electrode sheets and lithium-ion batteries of this treatment group are strictly consistent with those of treatment group 1A of Example 1.

[0045] Treatment Group 3A

[0046] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that when preparing the positive electrode sheets, the mass content of LFO in the positive electrode sheets is 5% (achieved by correspondingly reducing the content of LFP). In addition to the above differences, the operation steps of preparing the positive electrode sheets, negative electrode sheets and lithium-ion batteries of this treatment group are strictly consistent with those of treatment group 1A of Example 1.

[0047] Treatment Group 4A

[0048] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that when preparing the positive electrode sheets, the mass content of LFO in the positive electrode sheets is 10% (achieved by correspondingly reducing the content of LFP). In addition to the above differences, the operation steps of preparing the positive electrode sheets, negative electrode sheets and lithium-ion batteries of this treatment group are strictly consistent with those of treatment group 1A of Example 1.

[0049] Treatment Group 5A

[0050] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries with reference to the formula and method provided by treatment group 1A of Example 1. The difference from treatment group 1A of Example 1 is that when preparing the positive electrode sheets, the mass content of LFO in the positive electrode sheets is 20% (achieved by correspondingly reducing the content of LFP). In addition to the above differences, the operation steps of preparing the positive electrode sheets, negative electrode sheets and lithium-ion batteries of this treatment group are strictly consistent with those of treatment group 1A of Example 1.

[0051] Treatment Group 6A

[0052] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium ion batteries with reference to the formula and method provided by treatment group 3A of Example 1. The difference from treatment group 3A of Example 1 is that when preparing positive electrode sheets, this treatment group does not introduce primary particles larger than 2 μm into the positive electrode active material. The specific gradation is as follows: the mass content of primary particles of the positive electrode active material with a particle size of <0.2 μm is 50%, and the mass content of primary particles of the positive electrode active material with a particle size of 0.2 to 2 μm is 50%. In the positive electrode active material, the gradation of the positive electrode active material satisfies the conditions shown in Table 3. Specifically, this treatment group replaces 2 to 5 μm LFO with an equal mass fraction of 0.2 to 2 μm LFO, and the mass content of LFO in the positive electrode sheet in this treatment group is 5%. In addition to the above differences, the operation steps of preparing positive electrode sheets, negative electrode sheets and lithium ion batteries in this treatment group are strictly consistent with those of treatment group 3A of Example 1.

[0053] Table 3. Grading of positive electrode active materials in treatment group 6A

[0054] Particle size Quality content materials <0.2μm 50% LFP 0.2~2μm 50% LFP+LFO >2μm 0% /

[0055] Treatment Group 7A

[0056] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries with reference to the formula and method provided by treatment group 3A of Example 1. The difference from treatment group 3A of Example 1 is that when preparing positive electrode sheets, the gradation of the positive electrode active material in the positive electrode active material meets the conditions shown in Table 4, and the mass content of LFO in the positive electrode sheet is 5%. In addition to the above differences, the operation steps of preparing positive electrode sheets, negative electrode sheets and lithium-ion batteries in this treatment group are strictly consistent with those of treatment group 3A of Example 1.

[0057] Table 4. Grading of positive electrode active materials in treatment group 7A

[0058] Particle size Quality content materials <0.2μm 60% LFP 0.2~2μm 10% LFP >2μm 30% LFP+LFO

[0059] Comparative Group 1A

[0060] This comparative group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries according to the formula and method provided by treatment group 3A of Example 1. The difference from treatment group 3A of Example 1 is that when preparing positive electrode sheets, this comparative group replaces LFO with LFP of equal mass fraction; when preparing negative electrode sheets, artificial graphite is replaced with graphite of equal mass fraction. Except for the above differences, the operation steps for preparing positive electrode sheets, negative electrode sheets and lithium-ion batteries in this comparative group are strictly consistent with those of treatment group 3A of Example 1.

[0061] Test Example 1

[0062] 1. Test subjects

[0063] The lithium-ion batteries, positive electrodes and negative electrodes prepared in each treatment group and comparison group in Example 1.

[0064] 2. Test Method

[0065] (1) Volume energy density: refers to the volume energy density of a single cell, which is calculated using equations ① and ②.

[0066] Volume energy density (Wh / L) = total battery capacity (Wh) / volume (L)①

[0067] Total battery capacity (Wh) = discharge platform voltage (V) × capacity (Ah)②

[0068] (2) Compacted density of the positive electrode: The compacted density is calculated using formula ③.

[0069] Compacted density of positive electrode sheet = positive electrode coating surface density / thickness after cold pressing ③ 3. Test results

[0070] The test results of this test example are shown in Table 5. Based on the test data of each treatment group and comparison groups 1A to 3A of this test example, it can be seen that the lithium-ion battery provided by the present invention can further improve the energy density of the lithium-ion battery by introducing lithium iron phosphate and lithium-rich oxide into the positive electrode sheet and introducing artificial graphite into the negative electrode sheet. This shows that the lithium-ion battery provided by the present invention can significantly enhance its energy density by matching the positive electrode sheet with the negative electrode sheet.

[0071] It can be seen from the data of treatment groups 1A to 5A and comparison group 1A. As the mass content of lithium-rich oxide in the positive electrode active material increases, the energy density of the lithium-ion battery shows a trend of first increasing and then decreasing. When the lithium-rich oxide is too low, the active lithium ions released by the lithium-rich oxide during the first charge are not enough to make up for the irreversible lithium loss, so the energy density of the lithium-ion battery using it is close to that of the comparison group; and when the lithium-rich oxide is too high, the mass proportion of lithium iron phosphate in the active material is reduced from 97% to 77-87%, resulting in a decrease in the energy density of the lithium-ion battery. Furthermore, when the mass content of lithium-rich oxide in the positive electrode active material is 2.5% to 10%, the energy density of the lithium-ion battery is maintained at a good level.

[0072] In addition, compared with treatment group 2A, the primary particles in the positive electrode sheets provided by treatment group 6A are all less than or equal to 2μm. The lack of large particles will reduce the particle stacking effect, resulting in a significant decrease in the compaction density of the positive electrode sheets, which in turn leads to a decrease in the energy density of the lithium-ion battery. In treatment group 7A, due to the change in the intermediate value area of ​​the continuous grading, the unreasonable particle interval ratio cannot achieve the optimal stacking effect, resulting in a decrease in the compaction density of the positive electrode sheets, which in turn affects the energy density of the lithium-ion battery.

[0073] Table 5. Experimental data of test case 1

[0074] Group <![CDATA[Battery energy density / Wh L -1 > <![CDATA[The compaction density of the positive electrode sheet g / cm 3 > Treatment Group 1A 445 2.65 Treatment Group 2A 462 2.70 Treatment Group 3A 470 2.75 Treatment Group 4A 438 2.75 Treatment Group 5A 405 2.75 Treatment Group 6A 440 2.64 Treatment Group 7A 403 2.60 Comparative Group 1A 430 2.65

[0075] Example 2

[0076] Treatment Group 1B

[0077] The treatment group 1B of this embodiment refers to the formula and method provided by the treatment group 3A of Example 1 to prepare positive electrode sheets, negative electrode sheets and lithium-ion batteries. The difference from the treatment group 3A of Example 1 is that the formula for preparing positive electrode sheets in this embodiment is different, as shown in Table 6. In addition to the above differences, the operating steps for preparing positive electrode sheets, negative electrode sheets and lithium-ion batteries in this embodiment are strictly consistent with those of the treatment group 3A of Example 1. Among them, the ratio in Table 6 refers to: the mass ratio of the material for preparing the positive electrode sheet in the positive electrode sheet, and the mass ratio of the material for preparing the negative electrode sheet in the negative electrode sheet. In addition, the grading of the primary particles in the positive active material is shown in Table 7.

[0078] Table 6. Raw materials for preparing positive and negative electrodes of treatment group 1B

[0079]

[0080] Table 7. Mass content of each size of positive electrode active material in treatment group 1B

[0081]

[0082] Treatment Group 2B

[0083] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B of Example 2 is that when preparing positive electrode sheets, this treatment group uses lithium-rich oxides (LFO and LNO) in a mass ratio of LFO:LNO=20:80 (the total mass fraction of lithium-rich oxides remains unchanged, and the content of LFP in each level of formulation is increased or decreased to adapt to the content changes of LFO and LNO in each level of formulation). Except for the above differences, the operation steps of preparing positive electrode sheets, negative electrode sheets and lithium-ion batteries in this treatment group are strictly consistent with those of treatment group 1B of Example 2.

[0084] Treatment Group 3B

[0085] This treatment group prepares positive electrode sheets, negative electrode sheets and lithium-ion batteries with reference to the formula and method provided by treatment group 1B of Example 2. The difference from treatment group 1B of Example 2 is that when preparing positive electrode sheets, this treatment group uses lithium-rich oxides (LFO and LNO) in a mass ratio of LFO:LNO=80:20 (the total mass fraction of lithium-rich oxides remains unchanged, and the content of LFP in each level of formulation is increased or decreased to adapt to the changes in the content of LFO and LNO in each level of formulation). In addition to the above differences, the operating steps for preparing positive electrode sheets, negative electrode sheets and lithium-ion batteries in this treatment group are strictly consistent with those of treatment group 1B of Example 2.

[0086] Test Example 2

[0087] 1. Test subjects

[0088] The lithium-ion batteries prepared in each treatment group in Example 2.

[0089] 2. Test Method

[0090] The energy density of the battery and the compaction density of the positive electrode sheet were measured according to the method provided in Test Example 1.

[0091] (1) Cycle capacity retention rate: refers to the percentage of the discharge capacity at the nth cycle to the maximum discharge capacity during the entire cycle. The nth cycle capacity retention rate is calculated using formula ④.

[0092] Capacity retention rate (%) = discharge capacity at nth cycle (Ah) * 100% / maximum discharge capacity (Ah)④

[0093] (2) Calibrated gram capacity at different rates: At a calibration temperature of 25°C, use 6 different rate constant current discharges, namely 0.1C, 0.33C, 0.5C, 1C, 2C, and 3C, with a cut-off voltage of 2.5V. Record the discharge capacity Q. The calibrated gram capacity at different rates can be calculated using formula ⑤.

[0094] Rated gram capacity at different rates (mAh / g) = Q / mass of active material⑤ 3. Test results

[0095] The results of this test example are shown in Table 8.

[0096] The inventors found during the experiment that in order to improve the energy density of lithium-ion batteries, designing a high compaction density for the pole piece will affect the cycle performance or rate performance of the lithium-ion battery. Figure 1-2 From the test data, it can be seen that after introducing a specific proportion of LFO and LNO, it not only helps to maintain the high energy density of lithium-ion batteries, but also improves the cycle stability and rate performance of lithium-ion batteries. Specifically, although the compaction density of the positive electrode sheet gradually decreases, resulting in a decrease in the battery energy density, due to the addition of LNO, the rate performance of the batteries in treatment groups 1B to 3B is significantly improved compared with that in treatment group 3A, and the capacity retention rate of the long cycle 1400cyc is increased by about 1%. Therefore, the appropriate LFO and LNO grading relationship helps to improve the cycle stability and rate performance of the battery while maintaining the high energy density of the lithium-ion battery.

[0097] Table 8. Experimental data of treatment groups 1B to 3B in Example 2

[0098]

[0099]

[0100] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A lithium-ion battery with high energy density, characterized in that: The lithium-ion battery comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material comprises lithium iron phosphate and lithium-rich oxide; In the positive electrode sheet, the mass content of the lithium-rich oxide is 0.2 to 20%; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes artificial graphite.

2. The high energy density lithium ion battery according to claim 1, characterized in that: The positive electrode active material satisfies the following conditions: The primary particles of the positive electrode active material have a particle size of less than 0.2 μm, and their mass content is 35-45%; And / or, the positive electrode active material has a primary particle size of 0.2 to 2 μm and a mass content of 45 to 65%; And / or, the mass content of primary particles of the positive electrode active material having a particle size greater than 2 μm is 0 to 30%.

3. The high energy density lithium ion battery according to claim 1, characterized in that: The lithium-rich oxide includes at least one of lithium-rich lithium iron oxide, lithium-rich lithium nickel oxide, and lithium-rich lithium cobalt oxide.

4. The high energy density lithium ion battery according to claim 3, characterized in that: The particle size of the primary particles of the lithium-rich lithium iron oxide is 0.05 to 30 μm; And / or, the particle size of the primary particles of the lithium-rich lithium nickelate is 0.05 to 30 μm; And / or, the particle size of the primary particles of the lithium-rich lithium cobalt oxide is 0.05 to 30 μm.

5. The high energy density lithium ion battery according to any one of claims 1 to 4, characterized in that: The positive electrode active material satisfies the following conditions: In the primary particles of the positive electrode active material having a particle size of less than 0.2 μm, the lithium-rich oxide comprises lithium-rich nickel oxide; and / or, in the primary particles of the positive electrode active material having a particle size of 0.2 to 2 μm, the lithium-rich oxide comprises lithium-rich nickel oxide; And / or, in the primary particles of the positive electrode active material with a particle size greater than 2 μm, the lithium-rich oxide includes lithium-rich lithium ferrate.

6. The high energy density lithium ion battery according to claim 5, characterized in that: The lithium-rich oxide includes lithium-rich nickel oxide and lithium-rich iron oxide. Calculated by mass ratio, the lithium-rich iron oxide: lithium-rich nickel oxide = 5-8: 2-5.

7. The high energy density lithium ion battery according to claim 1, characterized in that: The particle size of the primary particles of the lithium iron phosphate is 0.02 to 6 μm.

8. The high energy density lithium ion battery according to claim 1, characterized in that: The compaction density of the positive electrode sheet is 2.2 to 3.1 g / cm 3 .

9. The high energy density lithium ion battery according to claim 1, characterized in that: The median particle size D of the artificial graphite 50 3~25μm.

10. The high energy density lithium ion battery according to claim 1 or 9, characterized in that: The compaction density of the negative electrode sheet is 1.4 to 1.9 g / cm 3 .

Citation Information

Patent Citations

  • Positive electrode material for lithium-ion battery and preparation method of positive electrode material

    CN107204461A

  • Synthesis process of lithium-rich oxide and lithium ion battery containing lithium-rich oxide

    CN108878849A

  • Fast-charging lithium ion battery

    CN109786810A

  • High-safety positive plate and lithium ion battery thereof

    CN112467107A

  • Composite electrode material and preparation method and application thereof

    CN115513424A

Cited By

  • High-energy-density lithium-ion battery

    WO2026103947A1